Antibiotic Stewardship in Residential Aged Care Facilities - Shohel, Mohammad (Curtin University, 2019)
Aged care residents are at increased risk of infections due to their frailty and comorbidities. This study aimed to identify and reduce the risk of antibiotic-related misadventure in this population. Particular medicines were associated with use of antibiotics, suggesting compromised immunity via numerous mechanisms. Potential interactions between antibiotics and residents’ other medicines were also identified, and may increase morbidity in this vulnerable group. Expanded scope of antimicrobial stewardship in aged care facilities is recommended.